2017
DOI: 10.1136/vetreccr-2017-000515
|View full text |Cite
|
Sign up to set email alerts
|

Abomasal hamartoma in a La Mancha wether

Abstract: An 18-month-old La Mancha wether was evaluated for progressive anorexia and lethargy of two weeks duration. Previous medical history had included suspected copper toxicity. Radiographs highlighted a distended rumen, and a rumenotomy yielded uniform ingesta devoid of normal stratification. The client elected for euthanasia and on postmortem examination an abomasal obstruction was identified. Histopathology demonstrated the presence of a pyloric hamartoma. This case describes the clinical presentation, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…Although some cases of post pantoprazole administration anaphylaxis (22,23) and edema (24,25) have been reported in humans, these clinical signs were not observed in our population. While the aim of this study was not to evaluate the clinical safety of pantoprazole in calves, the lack of observed adverse effects correlate with previously reported pantoprazole use in ruminants for case management of cattle (4,26), camels (27), sheep (15,28), yaks (29), and goats (30,31). Adverse effects of pantoprazole administration described people include hyponatremia (32), hypomagnesemia (33), as well as nephritis and hepatotoxicity (34).…”
Section: Discussionsupporting
confidence: 52%
“…Although some cases of post pantoprazole administration anaphylaxis (22,23) and edema (24,25) have been reported in humans, these clinical signs were not observed in our population. While the aim of this study was not to evaluate the clinical safety of pantoprazole in calves, the lack of observed adverse effects correlate with previously reported pantoprazole use in ruminants for case management of cattle (4,26), camels (27), sheep (15,28), yaks (29), and goats (30,31). Adverse effects of pantoprazole administration described people include hyponatremia (32), hypomagnesemia (33), as well as nephritis and hepatotoxicity (34).…”
Section: Discussionsupporting
confidence: 52%
“…However, that study did not evaluate safety with respect to adverse findings of pantoprazole administration in humans. Case reports involving ruminant species demonstrate use of pantoprazole in goats (3,18), a sheep (19), a beef bull (6), a camel (4), and a yak (5) with no reported complications from administration. Our study provides clinically relevant data to guide veterinary practitioners for the use of pantoprazole in hospitalized ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…In alpacas (2), pantoprazole has been shown to increase third-compartment pH when given at a dose of 1 mg/kg intravenously or 2 mg/kg subcutaneously with high bioavailability when administered subcutaneously. Currently, no pharmacokinetic, pharmacodynamic, or safety studies for pantoprazole exist for cattle, sheep, or goats, although case reports of the use of pantoprazole in individual ruminant animals without observed adverse effects or toxicities do exist (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…In alpacas [16], pantoprazole has been shown to increase third compartment pH when given at a dose of 1 mg/kg intravenously or 2 mg/kg subcutaneously. Among other ruminant species there are cases reporting the use of pantoprazole in a goat and a yak [6, 17]. Reported complications associated with pantoprazole in people include hyponatremia in hospitalized patients as well as neutropenia and thrombocytopenia with long-term use [18, 19].…”
Section: Discussionmentioning
confidence: 99%